Level of physical activity in men and women with chronic stroke. (3rd October 2019) - Vahlberg, Birgit; Bring, Annika; Hellström, Karin; Zetterberg, Lena
ABSTRACT: Introduction : Community-dwelling stroke survivors generally show low levels of physical activity (PA). An improved understanding of the factors influencing participation in PA after stroke is imperative to improve levels of PA. Furthermore, gender differences in PA have received little attention in stroke research. The objective of this study was to examine gender differences in PA, physical functioning and psychological factors and the association between these factors and PA in men and women 1–3-year post-stroke. Materials and methods : A total of 187 community-dwelling individuals with stroke (65–85 years old, 29% women) were included in a secondary analysis based on data from a cross-sectional study. The exclusion criteria were severe cognitive or language dysfunction or dementia. The level of PA was measured by the Physical Activity Scale for the Elderly. Physical function included balance, walking speed and mobility. Psychological factors included depression, health-related quality of life and fall-related self-efficacy. Falls and fear of falling were each measured with a single question. Results : There were no significant differences in PA levels between men and women. In multiple regression analyses, walking speed (p  < 0.001) was associated with PA in men, and balance ( p =  0.038) was associated with PA in women. Conclusions : The results indicate that strategies to increase PA levels 1–3-year post-stroke could be improved by considering gender-specific factors.